INTERAKSI SIMBOLIK PROSES PESTA PANEN â€œHAROA ANO LAAâ€ BUTON UTARA - Joko, Resti, La ode muh. Umran, (Jurnal Ilmu Komunikasi UHO : Jurnal Penelitian Kajian Ilmu Komunikasi dan Informasi, 2019)
The problem in this study is how the implementation of the Harvest Party "Haroa Ano Laa" and how the symbolic interaction forms the harvest party process "Haroa Ano Laa" in the Kasulatombi Village Community.The purpose of this study was to find out to find out the form of the harvest party "Haroa Ano Laa", to find out the form of symbolic interaction of the harvest party "Haroa Ano Laa". While the benefits in this study are expected to add theoretically, the results of this study are expected to be able to add and broaden insights on the meaning of symbolic interactions. Methodologically, it becomes additional information material for research, especially relating to symbols in communication. Practically, the results of the study are expected to provide input to the Kasulatombi village community.The subjects in this study were 614 families and informants in the study amounted to 6 people. Data collection in this study was conducted using observation, interview and documentation techniques which were then analyzed descriptively qualitatively.The results of this study that Haroa Ano Laa is one of the rituals carried out once a year by the Kasulatombi Village Community which aims to express gratitude and to remember the ancestors mandated by 2 friends including La Baundi and La Baura that the reading and reading ritual will be carried out as a sign to remember them. The harvest party process is the process of approaching the community with one another which is deliberately done by holding a harvest party. Key Words: Symbolic Interaction of Harvest Party Process "Haroano Ano Laa